Assessment of upper respiratory and gut bacterial microbiomes during COVID-19 infection in adults: potential aerodigestive transmission - Hafez Al-Momani; Andrew Nelson; Hadeel Al Balawi; Dua’a Al Balawi; Iman Aolymat; Ashraf I. Khasawneh; Hala Tabl; Ayman Alsheikh; AbdelRahman M. Zueter; Jeffrey Pearson; Christopher Ward (Scientific Reports)
Abstract SARS-CoV-2 is the viral pathogen responsible for COVID-19. Although morbidity and mortality frequently occur as a result of lung disease, the gastrointestinal (GI) tract is recognized as a primary location for SARS-CoV-2. Connections and interactions between the microbiome of the gut and respiratory system have been linked with viral infections via what has been referred to as the ‘gut-lung axis’ with potential aerodigestive communication in health and disease. This research explored the relationship between the microbiomes of the upper respiratory and GI tracts in patients with COVID-19 and examined Extraesophageal reflux (EOR), a mechanism which could contribute to dysregulated communication between the GI and respiratory tract (as identified in COVID-19). 97 patients with a laboratory diagnosis of COVID-19 infection, and 50 age-matched controls were recruited and stool, saliva and sputum were obtained from each participant. ELISA Pepsin tests and Reflux Symptom Index scores (RSI) were conducted for EOR assessment. DNA sequencing of the V4 region of the 16 S rRNA gene was performed for microbiome analysis. No differences were observed between the fecal microbiome’s alpha and Shannon diversity indices; however, a distinct microbial composition was observed in COVID-19 patients (when compared to the controls). The respiratory microbiota from individuals with COVID-19 demonstrated a statistically significant reduction in Shannon diversity and bacterial richness alongside an overall reduction in the prevalence of organisms from a typical healthy respiratory microbiome. Furthermore, the bacterial richness of the stool and sputum samples was significantly lower among COVID-19 patients admitted to ICU. A significantly higher RSI score and salivary pepsin level were detected among those with COVID-19. The data indicates that COVID-19 is associated with a dysregulation of both the gut and lung microbiome with a more marked perturbation in the lung, particularly among COVID-19 patients who had been admitted to the ICU. The presence of increased RSI scores, combined with elevated levels of Pepsin, suggests that increased micro-aspiration may occur, which is consistent with of under-recognized interactions between the GI and lung microbiomes in COVID-19 patients and requires additional study. Such studies would benefit from the insights provided by biological samples which reflect the continuum of the aerodigestive tract.